Synergistic Action of Cinnamomum verum Essential Oil with Sertraline - Alexia Barbarossa; Sabina Sblano; Antonio Rosato; Antonio Carrieri; Filomena Corbo; Maria Lisa Clodoveo; Giuseppe Fracchiolla; Alessia Carocci (MDPI AG, 2022)
Cinnamomum verum L. essential oil (CEO), commonly known as Ceylon cinnamon or cinnamon tree, is regarded as one of the most employed essential oils in the field of aromatherapy. It is usually applied externally as astringent, antipruritic, rubefacient, and anti-septic agent. Furthermore, both in vitro and in vivo research have demonstrated its numerous pharmacological effects, including the potentiality for treating neuralgia, myalgia, headache, and migraine. Several pieces of research also corroborated its significant antiviral and antimicrobial properties. Cinnamaldehyde, eugenol, caryophyllene, cinnamyl acetate, and cinnamic acid are the most representative compounds that are generally found in greater quantities in CEO and play a pivotal role in determining its pharmacological activities. Due to the global antibiotic resistance scenario and the dwindling amount of funding dedicated to developing new antibiotics, in recent years research has concentrated on exploring specific economic approaches against microbial infections. In this context, the purpose of this study was the investigation of the synergistic antibacterial activities of commercially available and chemically characterized CEO in combination with sertraline, a selective serotonin reuptake inhibitor (SSRI), whose repositioning as a non-antibiotic drug has been explored over the years with encouraging results. In vitro effects of the titled combination were assessed toward a wide panel of both Gram-positive and Gram-negative bacteria. The antimicrobial efficacy was investigated by using the checkerboard microdilution method. The interesting preliminary results obtained suggested a synergistic effect (fractional inhibitory index, FICI < 0.5) of sertraline in combination with CEO, leading to severe growth inhibition for all bacterial species under investigation.